Exercise physiology an integrated approach - Raven, Peter Bernard 1940-; Wasserman, David H.; Squires, William Jr. G.; Murray, Tinker D. (Wadsworth Cengage Learning, 2013)
This textbook provides definitive coverage of the effects of exercise on physiological systems in the context of the most recent research. Discusses relevant issues such as the role exercise plays in fighting the global pandemic of sedentary disease among all age groups including obesity, diabetes, and metabolic syndrome. Examples are integrated throughout the textbook linking principles of exercise physiology to strategies that can be used in real-life client situations.